2007
DOI: 10.1038/sj.jp.7211690
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nitric oxide in infants >1500 g and <34 weeks gestation with severe respiratory failure

Abstract: Objective: Inhaled nitric oxide (iNO) use in infants >1500 g, but <34 weeks gestation with severe respiratory failure will reduce the incidence of death and/or bronchopulmonary dysplasia (BPD).Study Design: Infants born at <34 weeks gestation with a birth weight >1500 g with respiratory failure were randomly assigned to receive placebo or iNO.Results: Twenty-nine infants were randomized. There were no differences in baseline characteristics, but the status at randomization showed a statistically significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 29 publications
3
49
0
1
Order By: Relevance
“…[10][11][12][13][14][15] Subsequently, several randomized clinical trials were undertaken. [16][17][18][19][20][21][22][23] Table 1 outlines the study population, entry criteria, and dose and duration of iNO treatment and summarizes the outcomes for all published randomized controlled trials. Only 1 small trial of 40 patients reported a beneficial effect on survival (Table 1).…”
Section: Use Of Ino In Preterm Infants With Respiratory Failurementioning
confidence: 99%
“…[10][11][12][13][14][15] Subsequently, several randomized clinical trials were undertaken. [16][17][18][19][20][21][22][23] Table 1 outlines the study population, entry criteria, and dose and duration of iNO treatment and summarizes the outcomes for all published randomized controlled trials. Only 1 small trial of 40 patients reported a beneficial effect on survival (Table 1).…”
Section: Use Of Ino In Preterm Infants With Respiratory Failurementioning
confidence: 99%
“…The respiratory state of these VLBW neonates was serious and life threatening with a mean OI of 36, hypercapnia (PaCO 2 71 mm Hg), and acidosis (arterial pH 7.11), in contrast to many clinical studies on patients with mild or moderate HRF [8,9,10,11,12,13,14,15,16]. Their cardiovascular status was also compromised.…”
Section: Discussionmentioning
confidence: 78%
“…However, there were limited improvements in the survival rate, incidence of chronic lung disease, and neurodevelopmental outcome of preterm neonates treated with iNO at different postnatal ages, doses, and durations [8,9,10,11,12,13,14,15,16]. The use of iNO remains experimental in preterm neonates [1,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, with respect to the optimal timing, previous studies [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] differ greatly due to their design ( table 1 ). Some authors report the age at enrolment, while others prefer to record the age at randomization or therapy beginning; nevertheless, in the majority of studies iNO was started within the first 48 h of life [7,[9][10][11][12][13][14][15][16][17][18]20] , and it was started later only by Subhedar and Shaw [8] (4-5 days of life) and Ballard et al [19] (7-21 days of life). Unfortunately, no studies compared the effects of starting iNO at different ages in preterm infants; therefore, the optimal timing for starting iNO is still unknown.…”
Section: Optimal Age Dose and Duration Of Ino Therapymentioning
confidence: 99%
“…In conclusion, it appears that from a methodological point of view these studies may be put into 3 categories: the studies in which iNO was given as an early prophylaxis [12,18] , the studies in which iNO was given as an early rescue treatment [9,11,14,15,17,20] , and the studies in which iNO was given as a late treatment [8,19] . Unfortunately, the usefulness of this classification is limited by the large differences remaining between the studies in each category (e.g.…”
Section: Clinical Studies On Ino Treatment In Preterm Infantsmentioning
confidence: 99%